If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -5y = 3 Solving 2x + -5y = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5y' to each side of the equation. 2x + -5y + 5y = 3 + 5y Combine like terms: -5y + 5y = 0 2x + 0 = 3 + 5y 2x = 3 + 5y Divide each side by '2'. x = 1.5 + 2.5y Simplifying x = 1.5 + 2.5y
| .5(25-x)=35 | | -2x+5y=-2 | | 4x+4=25-3x | | -5m=80 | | 3x+2=27-2x | | 9x+1=4x+9 | | 0.25ax=3ab | | lm(x+2)-ln(x+1)=1 | | 5x+7y=-2 | | 6x-29=35-10x | | x^3-8x^2+9x=72 | | 1+2x-5x^2=0 | | 3+9x=30 | | 4b^2-9b-46=9 | | 4v^2-10v-17=7 | | 5x-7-4x=6 | | 2n+17=-38-37n | | N^2-2n-18=-3 | | 16.94=3g+3.68 | | N^2-8n+23=8 | | P=2x-2y | | 1.32g-4=0.62 | | y=175+.1*225 | | 5y-5=2y-7+5 | | 6p+1=3(2p+3) | | 3(2g-15)+8g=11 | | X^2-8x+23=8 | | 4x-3x=2x+11 | | 4(x+6)+2=20+4x-6 | | 4m+m=15 | | -24+15-22z=31 | | 5x+6y=22 |